1995
DOI: 10.1159/000129413
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Liposomal Adriamycin for Metastatic Adenocarcinoma of the Liver

Abstract: A liposome-entrapped liposome form of Adriamycin (Lip-ADM) has been demonstrated to cause less myocardial and gastrointestinal toxicity than free ADM. In the present study, Lip-ADM prepared by the remote loading method was administered to 3 patients with metastatic adenocarcinoma of the liver via a reservoir with the catheter located in the proper hepatic artery. The primary tumor was gastric cancer in 2 patients and sigmoid colon cancer in 1. Lip-ADM was administered at doses of 10, 20 or 50 mg per time. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…11 Lip-ADM has also been reported to have an excellent clinical therapeutic effect on metastatic liver tumors from gastrointestinal cancer. 28 Pisani et al reported that approximately 400 000 people die of colorectal cancer in the world every year, 29 and liver metastases develop in approximately 60% of patients with colorectal cancer. Liver resection is currently the only treatment that offers long-term survival, following which the 5-year survival rates range from 25% to 40%; however, less than 20% of patients are candidates for resection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Lip-ADM has also been reported to have an excellent clinical therapeutic effect on metastatic liver tumors from gastrointestinal cancer. 28 Pisani et al reported that approximately 400 000 people die of colorectal cancer in the world every year, 29 and liver metastases develop in approximately 60% of patients with colorectal cancer. Liver resection is currently the only treatment that offers long-term survival, following which the 5-year survival rates range from 25% to 40%; however, less than 20% of patients are candidates for resection.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that local administration of liposomal Adriamycin through the hepatic artery to three patients with metastatic gastric adenocarcinoma significantly lowered common gastrointestinal and myocardial toxicity when compared to patients treated with the free drug. The patients tolerated the treatment with increased doses of Adriamycin (41). A reduction of renal toxicity and an increase in hepatic uptake of cyclosporine (CsA) have been shown for CsAcontaining liposomes in a liver transplant model in rats (42).…”
Section: Attenuation Of Drug Side Effectsmentioning
confidence: 99%
“…Despite these considerations, interest in the use of DXR for the treatment of advanced colon carcinoma has not faded. For instance, some authors have proposed to exploit the pharmacokinetic advantages provided by a particular drug delivery formulation such as liposomes in the DXR‐based locoregional treatment of liver metastases [8, 9, 10]. We are conducting a pilot study on pelvic perfusion with DXR in patients affected with locally advanced colorectal cancer, and the preliminary results appear encouraging (manuscript in preparation).…”
mentioning
confidence: 99%